Interactive Multimedia Inquiry Based on Local Wisdom: Alternative Media to Improve Students' Environmental Care Attitude - Agus Ramdani; A. Wahab Jufri; Jamaluddin Jamaluddin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The students' environmental care attitude is still low. One of the factors that cause environmental damage is the lack of awareness of students in the importance of disposing of waste in its place and knowledge in managing waste. In addition to the problem of students' environmental care, learning in schools is also still rarely associated with learning materials with the surrounding environment (local wisdom). The research aims to develop an interactive multimedia inquiry that integrates practical and effective local wisdom to improve students' environmental care attitudes. This research is a development research using a 4D development model. The environmental care attitude questionnaire instrument was developed referring to 4 indicators, namely: maintaining class cleanliness, maintaining school cleanliness, developing empathy for all forms of life and maintaining plants at school. Data collection techniques using a questionnaire instrument. The practicality data analysis technique uses practicality percent and the effectiveness of interactive multimedia inquiry is analyzed using normalized gain. The results showed that the teacher's response to multimedia products was categorized as good because it was in accordance with learning needs by utilizing technology. Students' responses to multimedia are categorized as good because the tasks given are in accordance with the experiences of students in both the social and school environment. Based on the results of the analysis of the effectiveness test, it showed that the experimental class taught using interactive multimedia inquiry based on local wisdom obtained an increase in environmental care attitudes which was higher than the control class taught without using interactive multimedia based on local wisdom, it obtained an increase with moderate criteria. Based on this description, it can be concluded that interactive multimedia inquiry based on local wisdom is practical and effective to improve students' environmental care attitudes.